2012
DOI: 10.1039/c1cp22271f
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical evaluation of possible transition metal electro-catalysts for N2reduction

Abstract: Theoretical studies of the possibility of forming ammonia electrochemically at ambient temperature and pressure are presented. Density functional theory calculations were used in combination with the computational standard hydrogen electrode to calculate the free energy prole for the reduction of N 2 admolecules and N adatoms on several close-packed and stepped transition metal surfaces in contact with an acidic electrolyte. Trends in the catalytic activity were calculated for a range of transition metal surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
1,550
5
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,302 publications
(1,620 citation statements)
references
References 49 publications
61
1,550
5
4
Order By: Relevance
“…According to the calculations of Skúlason et al, 55 no catalytic activity is expected above -0.5 V vs.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…According to the calculations of Skúlason et al, 55 no catalytic activity is expected above -0.5 V vs.…”
Section: Resultsmentioning
confidence: 93%
“…Heterogeneous catalysts that bind nitrogen atoms to their surfaces more strongly than they bind hydrogen atoms may reduce hydrogen evolution, but this seems likely to require employing catalysts that are not optimal for the nitrogen reduction reaction itself, such as the early transition metals. 55 Then again,…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…20,30,31 Most recently, Licht and co-authors demonstrated significantly higher ammonia production rates and faradaic efficiencies in a molten hydroxide electrolyte cell with a nano-Fe 2 O 3 catalyst and at slightly elevated temperatures (105 °C-200 °C). 13,18 Initial theoretical modeling efforts by Howalt, Skúlason and co-authors 32,33 (Fig. 4, volcano plot representation of theoretical predictions) suggested that while ruthenium may be optimal for nitrogen reduction, several nonprecious metals such as iron, nickel, and cobalt might be useful especially in combination.…”
Section: The Need For Selective Catalystsmentioning
confidence: 99%
“…Employing these trends for the computational screening [3,59] of advanced metal nitride redox materials is outlined. Figure 7a decomposes the electronic interaction of the metal dopant, as an example for doped Mo 2 N, into the metalprojected s-, p-and d-orbitals.…”
Section: Electronic Structure Descriptorsmentioning
confidence: 99%